2013
DOI: 10.7314/apjcp.2013.14.8.4549
|View full text |Cite
|
Sign up to set email alerts
|

Lymphangiogenic and Angiogenic Microvessel Density in Chinese Patients with Gastric Carcinoma: Correlation with Clinicopathologic Parameters and Prognosis

Abstract: The incidence of gastric cancer worldwide, and in particular in developing countries, has shown a marked increase. Poor prognosis of gastric cancer patients occurs due to the rapid metastasis of the disease via the lymphatic and blood vessels. The aim of this study was to investigate the expression and the clinical significance of D2-40 and CD34 in human gastric cancer. D2-40 and CD34 expression wasdetected in 1,072 cases of Chinese patients with gastric carcinoma using immunohistochemistry. The lymphatic vess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 16 publications
1
12
0
Order By: Relevance
“…In all clinicopathologic parameters, lymph node metastasis was the most independent factor as a prognostic biomarker (p=0.011) ( Table 2). In accordance with our results, previous study found TNM and lymph node metastasis are all independent prognostic factors affecting the survival of patients with gastric cancer (Cao et al, 2013).…”
Section: Annexin A3 Is An Independent Prognostic Biomarker For Poor Osupporting
confidence: 93%
“…In all clinicopathologic parameters, lymph node metastasis was the most independent factor as a prognostic biomarker (p=0.011) ( Table 2). In accordance with our results, previous study found TNM and lymph node metastasis are all independent prognostic factors affecting the survival of patients with gastric cancer (Cao et al, 2013).…”
Section: Annexin A3 Is An Independent Prognostic Biomarker For Poor Osupporting
confidence: 93%
“…Lymphatic vessel density (LVD) is a quantitative measure of tumor lymphangiogenesis and is measured by directly counting lymphatic vessels. It has been reported that high LVD in gastric cancer correlates with regional lymph node metastasis and poor prognosis [ 9 11 ]. However, in these studies, the effect of lymphangiogenesis associated with intratumoral lymphatics or peritoumoral lymphatics was not evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Growing evidence indicates that tumor lymphangiogenesis and angiogenesis play important roles in the progression of GC [ 34 ]. In addition, high lymphatic vessel density and microvessel density are shown to be correlated with a poor survival rate in human GC [ 35 ]. Therefore, other than lymphovascular invasion of tumor cells as an important prognostic factor in GC, targeting tumor-associated lymphangiogenesis and angiogenesis may also provide a novel therapeutic approach.…”
Section: Discussionmentioning
confidence: 99%